Localized Leishmania Lymphadenitis Etiologic Agent Identified as Leishmania tropica Using Gene Sequencing - Moeinadin Safavi; Shahriar Dabiri (Iranian Society of Pathology, 2016)
Leishmaniasis include several clinical manifestations, mostly cutaneous, visceral and mucosal (1, 2). Various species can lead to diverse clinical presentations. Thus species identification contribute to proper management (3). Localized Leishmania Lymphadenitis (LLL) is a distinct entity in clinicopathologic field presenting with isolated lymphadenitis and possible cocomitant cutaneous lesion in the absence of systemic visceral involvement (4). Species identification has been acceptable by conventional microscopic evaluation, serologic methods such as isoenzyme and monoclonal antibody detection and particularly PCR. However, definite identification and confirmation of parasite without gene sequencing have always been doubted (5).